Evaluation of cooking performance, structural properties, storage stability and shelf life prediction of high-moisture wet starch noodles. (30th September 2021) - Yang, Sha; Zhang, Meng-Na; Shan, Chang-Song; Chen, Zhi-Gang
Graphical abstract: Highlights: Micro- and molecular structure of dried and wet starch noodles are studied. Storage stability and shelf-life prediction of wet starch noodles are evaluated. Cooked wet noodles exhibit more evenly network and better cooking properties. Wet starch noodles have more complete crystallites and ordered structure. The established model was suitable for predicting shelf life of wet starch noodles. Abstract: Cooking performance, micro- and molecular structure, storage stability and shelf-life prediction of high-moisture wet starch noodles (SN) were investigated. SEM images revealed that compared to dried SN, cooked wet SN had more evenly honeycomb-like network with smaller size of pores, indicating stronger interaction among molecules and causing favorable cooking performance. XRD and ATR-FTIR results evidenced that wet SN contained more complete crystallites and higher proportion of crystalline region. During storage, the quality decay of wet SN was mainly associated to the increment of total aerobic viable count (TAVC), titrable acidity and amylase, as well as the decreased textural hardness, overall acceptability and lightness. Based on TAVC, titrable acidity and overall acceptability, predicted shelf-life of vacuum-packed wet SN at 25 °C was 15.31, 21.54 and 16.65 weeks respectively, with relative error all within 20%, proving that the validated model could be an effective tool for monitoring the shelf-life of wet SN.